2016
DOI: 10.1515/bjreecm-2016-0011
|View full text |Cite
|
Sign up to set email alerts
|

Social Partner Involvement in Latvia Special Economic Zones

Abstract: Abstract. With increasing global competitiveness, countries must have instruments to attract and keep businesses. One way involves attracting a core of foreign investors with the help of special economic zones (SEZs) and integrating them in local economy, causing industrial clustering. The aim of this research is to lay the groundwork for a comprehensive analysis of clustering potential in Latvia via its special economic zones. The empirical research relied on survey results conducted among 27 business associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The potential for clustering effect occurs from the involvement of businesses both within and outside of SEZs with each other and establishing mutual supply, labour and knowledge networks. Early research conducted in this area has revealed that there is very little obvious involvement between the businesses in SEZs and members of the various Latvian business associations and their members (Gulbis & Geipele, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The potential for clustering effect occurs from the involvement of businesses both within and outside of SEZs with each other and establishing mutual supply, labour and knowledge networks. Early research conducted in this area has revealed that there is very little obvious involvement between the businesses in SEZs and members of the various Latvian business associations and their members (Gulbis & Geipele, 2016).…”
Section: Resultsmentioning
confidence: 99%